Pengaruh Citra Merek Dan Desain Produk Terhadap Keputusan Pembelian Produk Kosmetik Wardah di Kota Jakarta Barat - Utami, Alfia Nur; Sucipto, Rakhmat Hadi; Annisa, Tri Indah (CV Warnak Johanna Nusantara, 2025)
In the context of marketing, purchasing decisions represent a form of consumer response to their perceptions of brand quality and product appearance. This study aims to examine and prove the effect of brand image and product design on purchasing decisions, both partially and simultaneously. The method used is a quantitative approach with a survey technique involving 96 respondents through a Likert scale questionnaire. Data analysis was carried out using multiple linear regression with the assistance of SPSS version 25 software. The results show that the brand image variable has a significant partial effect on purchasing decisions, with a t-value of 8.691 > t-table 1.661 and a significance level of 0.000 < 0.05, thus the first hypothesis (H1) is accepted. The product design variable also has a significant partial effect on purchasing decisions, with a t-value of 7.687 > t-table 1.661 and a significance level of 0.000 < 0.05, thus the second hypothesis (H2) is accepted. Simultaneously, brand image and product design significantly influence purchasing decisions, with an F-value of 66.760 > F-table 3.09 and a significance level of 0.000 < 0.05, thus the third hypothesis (H3) is accepted. The coefficient of determination (R²) of 0.589 indicates that brand image and product design are able to explain 58.9% of the variation in purchasing decisions, while the remaining 41.1% is influenced by other factors outside this study.